Lentil Ascochyta blight and breeding for its resistance - Ye, G.; McNeil, D.L.; Hill, G.D. (New Zealand Plant Protection, 2000)
This paper summarises existing studies of the genetics of resistance of lentils to Ascochyta blight and the genetic variation among pathogen populations with particular emphasis on the results from our programme Breeding methods are discussed Six pathotypes have been identified Resistance is mainly under the control of major genes but minor genes also play a role Current breeding programs are based on crossing resistant cultivars with high yield cultivars and multilocation testing Gene pyramiding exploring slow blighting and partial resistance and the use of genes from wild relatives will be the methods used in future